Peran Servant Leadership dan Burnout terhadap Perilaku Kerja Inovatif - Afriza, Izyar; Mansyur, Anwar (Ekonomis: Journal of Economics and Business, 2024)
In this highly competitive era, whether Servant Leadership and burnout are sufficient to address challenges in the workplace, corporate leaders need to master complex leadership skills to survive in the intense competition. This research aims to determine the impact of servant leadership and burnout on the innovative work behavior of employees at PT Triconville - Demak Factory. The study is designed using a quantitative method; the sample used for this research is purposive sampling, with a total of 101 respondents. Data collection techniques involve the use of a questionnaire, and the stages of testing in this research include descriptive test, instrument test, model test, and hypothesis test using the SPSS program. The results of this research indicate that servant leadership has a positive and significant impact on innovative work behavior, while burnout has a negative and non-significant impact on innovative work behavior.